Who is maud dixon? eaudiobook A novel. - Andrews, Alexandra (2021)
"Part Patricia Highsmith, part All About Eve and pure fun."―Maria Semple Florence Darrow has always felt she was destined for greatness, but after a disastrous affair with her married boss, she starts to doubt herself. All that changes when she sets off for Morocco with her new boss, the celebrated but reclusive author Maud Dixon. Amidst the colorful streets of Marrakesh and the wind-swept beaches of the coast, Florence begins to feel she's leading the sort of interesting, cosmopolitan life she deserves. But when she wakes up in the hospital after a terrible car accident, with no memory of the previous night—and no sign of Maud—a dangerous idea begins to take form. . . A Best Book of the Year: New York Times, NPR, New York Post , Entertainment Weekly, CrimeReads